A Strategy For Coal Mine Respirable Dust Sampling Using Multi-Stage Impactors For Characterization Purposes (c39a8ed9-5c5f-43b1-8697-64d932a2f1c0) - Changwoo Lee; Jan M. Mutmansky (Society for Mining, Metallurgy & Exploration, 1986)
Introduction Recognition of Coal Workers' Pneumoconiosis (CWP) as a major occupational disease has affected various aspects of the coal mining industry in the United States as well as in almost all major coal producing countries. Regulations related to the control of coal mine dust forced mine operators to modify their mining and ventilation practices. As the coal production record of the last 15 years shows, this had both direct and indirect impacts on the productivity and production costs. To identify the causes of CWP, many research efforts have been made through- out the world. Most of these studies were epidemiological in nature, attempting to pinpoint exposure and seam variables that affected the incidence of the disease. Other studies have been oriented toward the elemental and mineralogical composition of the coal dust in the mine atmosphere and in the miners' lungs. These studies indicate that there may exist some relationships between the characteristics of the coal mine dust and the prevalence of the disease. Some of the variables that are thought to affect the occurrence of CWP are the mass of the dust in the working place, the rank of the coal, the existence of certain trace elements, the free silica content of the coal, and the existence of other minerals in the respirable dust. A more complete description of these previous re- search studies has appeared elsewhere (Mutmansky and Lee, 1984). The behavior of particles in the human lung is known to be governed by their aerodynamic diameter, which is defined as the diameter of a hypothetical spherical particle with unit density that exhibits the same settling velocity as the given particle. Because of this fact, the aerodynamic size distribution of coal mine dust is one of the parameters to be determined along with the other physical, elemental, and mineralogical characteristics. The objective of this paper is to establish a strategy for providing coal mine respirable dust samples for characterization purposes using instruments that classify according to the aerodynamic diameter. In addition, several findings concerning characterization methods will be presented. Choice of Samplers Most of the gravimetric dust collection devices that can be utilized in a mine environment can be